CD4+CD25+Foxp3+IFN-γ+ human induced T regulatory cells are induced by interferon-γ and suppress alloresponses nonspecifically - Daniel, Volker; Sadeghi, Mahmoud; Wang, Haihao; Opelz, Gerhard (Human immunology, 2011)
Interferon-γ (IFN-γ)-producing CD3+CD4+CD25+Foxp3+ peripheral blood lymphocytes (PBL) are more frequently detectable in patients with good than in patients with impaired long-term kidney graft function, suggesting an immunoregulatory role of this induced T regulatory (iTreg) subtype. Herein, the in vitro function of separated CD3+CD4+CD25+Foxp3+IFN-γ+ PBL that were induced by phorbol 12-myristate 13-acetate (PMA)/ionomycin or alloantigenic stimulation was investigated using cell coculture techniques and flow cytometry. CD4+CD25+Foxp3+ PBL with intracellular IFN-γ production increased to 26% in cell cultures stimulated with PMA/ionomycin for 6 hours. Recombinant IFN-γ augmented and anti-IFN-γ monoclonal antibody blocked induction of CD4+CD25+Foxp3+IFN-γ+ PBL, suggesting their IFN-γ-dependent induction. In addition, CD4+CD25+Foxp3+IFN-γ+ PBL produced immunosuppressive interleukin (IL)-10, transforming growth factor-β, and IL-4 intracellularly and expressed both IFN-γ and IFN-γ receptors (CD119) on the cell surface, allowing separation of CD4+CD25+IFN-γ+ PBL with 98% purity. Addition of enriched CD4+CD25+IFN-γ+ PBL to autologous PMA/ionomycin stimulated PBL decreased blast formation (p < 0.05), indicating suppression of cell proliferation by CD4+CD25+IFN-γ+ PBL. CD4+CD25+IFN-γ+ PBL separated from primary mixed leukocyte cultures (MLC) and added to autologous or third-party secondary MLC suppressed allogeneic T-cell activation nonspecifically (p < 0.05). We conclude that CD4+CD25+Foxp3+IFN-γ+ PBL are induced by IFN-γ, making them sensors for IFN-γ and initial immune responses. Circulating CD4+CD25+Foxp3+IFN-γ+ PBL could suppress allogeneic T-cell responses in patients and may be involved in inhibition of the posttransplant alloresponse.